PENGARUH TYPICAL PERSON ENDORSER DALAM IKLAN SABUN MANDI LIFEBOUY VERSI LEBIH MUTAKHIR TERHADAP KEPUTUSAN PEMBELIAN PADA IBU RUMAH TANGGA DI KELURAHAN SIMPANG BARU KECAMATAN TAMPAN KOTA PEKANBARU - Mulyanda, Yodi Afrial; ", Rumyeni (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
In keeping with the S-R (Stimulus-Response) which basically express their reaction to the result of the stimulus which in this case is given by the mass media. There is a close link between media messages with the reaction or response from the audience. This means that the stimulus / television advertising on television advertising to the organism / consumer will produce a response. The purpose of this research is to determine how much Effect Typical Person Endorser in Lifebuoy Soap Ads More Sophisticated against Purchase Decision On Housewife in Kelurahan Simpang Baru Kecamatan Tampan. The method used in this research is quantitative method with a profound observation, researchers collected data using questionnaires. The location of this research in Kelurahan Simpang Baru Kecamatan Tampan. The total sample for this study of 100 respondents were obtained from the formula Slovin, and the sampling itself using accidental sampling technique. To find out how much the relationship between the two variables, the researchers use Person Product Moment correlation analysis. As for the data processing questionnaires, conducted using Statistic Program Product Of Service Solution (SPSS) Windows version 18. These results indicate that the effect of the Endorser Typical Person Lifebuoy Soap Ads More Sophisticated against Purchase Decision On Housewife in Kelurahan Simpang Baru Kecamatan Tampan, , That the value of R = 0.074 and coefficient of determination (Rsquare) is 0,005 result of squaring the correlation coefficient of 0.074 x 0.074. The figure shows the understanding that the contribution of variables influence the use of typical person on purchasing decisions obtained is 5% with a very weak effect category. Keywords: Typical Person Endorse, Purchase Decision